2014
DOI: 10.1016/j.scitotenv.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the water supply:demand ratios in a Mediterranean basin under different global change scenarios and mitigation alternatives

Abstract: Spatial differences in the supply and demand of ecosystem services such as water provisioning often imply that the demand for ecosystem services cannot be fulfilled at the local scale, but it can be fulfilled at larger scales (regional, continental). Differences in the supply:demand (S:D) ratio for a given service result in different values, and these differences might be assessed with monetary or non-monetary metrics. Water scarcity occurs where and when water resources are not enough to meet all the demands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(104 citation statements)
references
References 58 publications
6
94
0
4
Order By: Relevance
“…In particular, this model was developed to provide decision makers with a trade-off of ecosystem services to compare the impacts of the changes in land cover or climate [30]. InVEST Water Yield (InVEST-WY) is one of the modules of the InVEST model to estimate water supply, demand and hydropower [31,32] and has been used in previous studies in Korea [33,34]. This study aims to identify the time series changes in forest water supply; thus, the InVEST-WY model was considered the most appropriate one as it allows the spatial-temporal change analysis.…”
Section: Invest Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this model was developed to provide decision makers with a trade-off of ecosystem services to compare the impacts of the changes in land cover or climate [30]. InVEST Water Yield (InVEST-WY) is one of the modules of the InVEST model to estimate water supply, demand and hydropower [31,32] and has been used in previous studies in Korea [33,34]. This study aims to identify the time series changes in forest water supply; thus, the InVEST-WY model was considered the most appropriate one as it allows the spatial-temporal change analysis.…”
Section: Invest Modelmentioning
confidence: 99%
“…There is no change in other land cover types, but the forest area has been reconstructed Sustainability 2017, 9, 1017 6 of 18 every year. The coefficients of the biophysical table were determined according to the land cover information, and the K c coefficients of the forest area were set to 1 based on the previous studies [31,32].…”
Section: Input Data and Parameters Of The Invest Modelmentioning
confidence: 99%
“…They found that the model was sensitive to climate variables, but less so to the Z parameter (see model description). Similarly, Boithias et al (2014) and Terrado et al (2014) reflect on the sensitivity of the model to climate inputs and calibrate the model based on the climate parameters and return flows. The conclusions of these studies are often context-specific and lack a quantitative estimate of the model's structural uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of water demand and availability was mapped to correctly reproduce the spatial heterogeneity of water shortage in each study area: water stress assessments can vary depending on the spatial or temporal scale (Boithias et al, 2014). Thus, it is essential to properly account for the main heterogeneities in water demand and availability.…”
Section: Mapping Resource and Demand Managementmentioning
confidence: 99%